Life-history of Palaeoloxodon antiquus reveals Middle Pleistocene glacial refugium in the Megalopolis basin, Greece - Effrosyni Roditi; Hervé Bocherens; George E. Konidaris; Athanassios Athanassiou; Vangelis Tourloukis; Panagiotis Karkanas; Eleni Panagopoulou; Katerina Harvati (Scientific Reports, 2024)
Abstract The Balkans are considered a major glacial refugium where flora and fauna survived glacial periods and repopulated the rest of Europe during interglacials. While it is also thought to have harboured Pleistocene human populations, evidence linking human activity, paleoenvironmental indicators and a secure temporal placement to glacial periods is scant. Here, we present the first intra-tooth multi-isotope analysis for the European straight-tusked elephant Palaeoloxodon antiquus, on an adult male individual excavated in association with lithic artefacts at the MIS 12 site Marathousa 1 (Megalopolis basin, Greece). The studied find also exhibits anthropogenic modifications, providing direct evidence of hominin presence. We employed strontium, carbon and oxygen isotope analysis on enamel bioapatite to investigate its foraging and mobility behaviour, using a sequential sampling strategy along the tooth growth axis of the third upper molar, to assess ecological changes during the last decade of life. We found a geographically restricted range, in a C3-dominated open woodland environment, and relatively stable conditions over the examined timeframe. Our results show that, despite the severity of the MIS 12 glacial, the Megalopolis basin sustained a mesic habitat, sufficient plant cover and limited seasonal fluctuations in resource availability, pointing to its role as a glacial refugium for both fauna and hominins.